The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/aem.72.3.1833-1842.2006
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Transmission ofSalmonella entericaSerovar Typhimurium in an Outdoor Organic Pig Farming Environment

Abstract: It was investigated how organic rearing conditions influence the Salmonella enterica infection dynamics in pigs and whether Salmonella persists in the paddock environment. Pigs inoculated with S. enterica serovar Typhimurium were grouped with Salmonella-negative tracer pigs. Bacteriological and serological testing indicated that organic pigs were susceptible to Salmonella infections, as 26 of 46 (56%) tracer pigs turned culture positive. An intermittent and mainly low-level excretion of Salmonella (<100 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 52 publications
4
61
1
1
Order By: Relevance
“…These results may suggest that United Kingdom salmonellosis outbreaks associated with lettuce were not the result of preharvest contamination (1,13,21,22) or that soil was not the contamination route, as reported in the 2005 lettuce salmonellosis outbreak whose crop was irrigated with sewage (12). Although S. enterica can survive in soil for extended periods (17), preharvest contamination of leafy greens may be more likely from other routes, e.g., irrigation water.…”
mentioning
confidence: 74%
“…These results may suggest that United Kingdom salmonellosis outbreaks associated with lettuce were not the result of preharvest contamination (1,13,21,22) or that soil was not the contamination route, as reported in the 2005 lettuce salmonellosis outbreak whose crop was irrigated with sewage (12). Although S. enterica can survive in soil for extended periods (17), preharvest contamination of leafy greens may be more likely from other routes, e.g., irrigation water.…”
mentioning
confidence: 74%
“…Higher prevalence of Salmonella in pigs during the final stages of production is of greater concern from a public health and food safety perspective. Only a few studies have been conducted to highlight the prevalence of Salmonella in the ABF environment versus that in the conventional farm environment (6,7,9,32). In the ABF farm environment, Salmonella was detected only in three feed and two water samples at nursery 1 and finishing stages, in contrast to the conventional farm, for which positive environmental samples were widely represented by water, soil, feed, floor swabs, lagoon, and truck at different stages of production.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported that soil microbial communities respond to the presence of heavy metals and organic pollutants (1)(2)(3)(4)(5)(6). Increasing numbers of studies in recent years have also been conducted on soil biopollution by pathogenic microorganisms, including viruses, protozoa, and bacteria such as Escherichia coli O157:H7, Salmonella spp., and Listeria monocytogenes (7)(8)(9). E. coli O157: H7, a significant pathogen carried naturally by animals, has been shown to pose a significant threat to environmental safety and public health because of its low infective dose (as few as 10 cells) and its high pathogenicity in watery diarrhea, hemorrhagic colitis, hemorrhagic-uremic syndrome, thrombotic thrombocytopenic purpura, etc.…”
mentioning
confidence: 99%